Convergencia del ingreso: una aplicación al Tratado de Libre Comercio Ecuador — Estados Unidos - Marcillo Chasy, Jennifer (2004)
This document presents a dynamic simulation model whose study period is 36 years. Said model shows how in a context of trade opening -like the Free Trade Agreement between Ecuador and the United States- the per capita income of a developing economy can reach or even exceed the per capita income of a developed economy. The study emphasizes that there may be convergence in income as long as there is a greater accumulation of human capital in the developing economy, along with an adequate period of tariff reduction.